A technical note on unconfined compressive strength (UCS) of black cotton soil reinforced with hydrophobically-treated bamboo fibres - Sumit Kumar; Brahmdeo Yadav; Rohit Raj (Discover Sustainability)
Abstract This study explores hydrophobically-treated bamboo fibres effectiveness in improving black cotton soil’s unconfined compressive strength (UCS). Traditional soil stabilisation technologies like lime and cement increase soil strength while raising environmental and economic concerns. Bamboo fibres, known for their high tensile strength and environmental friendliness, provide a sustainable alternative. However, because of their hydrophilic character, they must be treated to perform as soil stabilisers effectively. Black cotton soil samples were blended with varied percentages of treated bamboo fibres (1%, 1.5%, 2%, and 2.5%) and tested for UCS after 0, 14, and 28 days of air curing. According to the data, adding bamboo fibres significantly improved UCS, especially when the fibre level was 2%. At 0 days of curing, UCS increased by 65% with 1% fibre content. The UCS improved significantly at 14 and 28 days, with the ideal 2% fibre content yielding 59% and 67% increases, respectively. Higher fibre content (2.5%) resulted in diminishing results due to probable poor mixing and lower cohesiveness. The study shows that hydrophobically-treated bamboo fibres considerably improve the strength of black cotton soil, providing a sustainable and environmentally friendly alternative to standard stabilisation methods. This approach fits with environmental aims and promotes sustainable construction practices, making it appropriate for places with expansive soils. The findings emphasize the potential of employing treated natural fibres for soil stabilisation, which will help improve green engineering solutions in geotechnical engineering.